Wildlife management and conservation in Vietnam: From policy to practice - Nguyễn Thị, V.A.; Nguyễn Thị, T.A.; Pham Thu Thuy; Tăng Thị, K.H. (Center for International Forestry Research, 2021)
In an increasingly complex international, regional, national and local context, Vietnam is working hard to perfect the legal framework and improve the effectiveness of wildlife conservation and management policies. In addition to demonstrating national policies are harmonized with and regional regulatory frameworks improve international policy implementation effectiveness and analyze opportunities challenges for wildlife management and conservation thereby perfecting the legal document system, removing barriers to legal policy effectiveness. Based on a review of secondary documents and interviews with experts, this report was prepared with three main objectives: (i) Review of current documents related to wildlife conservation and management in Vietnam. Vietnam; (ii) Evaluate the effectiveness of the implementation of these policies and (iii) propose policy directions to improve the effectiveness of conservation and management policies and ensure the well-being of people.